Drunkenness and Regretted Online Social Risk Behaviors: The Role of Social Drinking Motives and Positive Urgency - González Ponce, Bella (2023)
Background: Alcohol use and the use of social media and other forms of digital communications is characteristic of young adults. The present study prospectively examined the relationship between social drinking motives and positive urgency and the engagement in regretted online social risk behaviors while drunk (having posted on social media, called or texted someone, or been visibly drunk in a photo) among a community sample of young adults. Methods: Using a targeted sampling procedure, we accessed a baseline sample of 360 young adults aged 18–25 years old from the community. Of these, 339 (mean age: 21.1 [SD = 2.21]; female = 50.7%) completed 2-month follow-up measures. Results: Social drinking motives and the tendency to act impulsively under conditions of positive affect (i.e. positive urgency) were measured at baseline, and frequency of regretted online social risk behaviors were measured at follow-up. Results showed that baseline social drinking motives were positively associated with all three regretted online social risk behaviors examined at follow-up. Higher baseline positive urgency scores were associated with a higher frequency of regretted posting on social media and calling or texting someone while drunk at follow-up. Conclusions: Our findings support the inclusion of positive urgency and social drinking motives as key components of preventive interventions aimed at reducing potential negative consequences of using social media and other forms of digital communications while under the effects of alcohol.